SAAT PARASIT MEMBASMI PARASIT: UJI EFEKTIVITAS EKSTRAK BENALU SEBAGAI TERAPI MALARIA BARU - Budi, Danang Setia; Baskara, Anak Agung Ngurah Nata; Putra, Pramana Pananja; Faiqoh, Zulfa; Solikhah, Eti Nurwening (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
Nowadays, the antimalarial drug used showed resistances. Scientists look for new drugs by research especially using herbal plans. The mistletoe(Dendrophthoe pentandra) is previously known having antimalarial activity. This study was conducted to determine in vitro antiplasmodial activity, mechanism of heme polymerase inhibition, and cytotoxicity of water and ethanol extracts of Dendrophthoe pentandra against Vero cells.The results showed that water and ethanol extract of Dendrophthoe pentandra has in vitro antiplasmodial activity, inhibition of polymerase heme, and cytotoxic effect on Vero cells with IC50 values.It can be concluded that Dendrophthoe pentandra has potency as an antiplasmodial.Keywords :Dendrophthoe pentandra, antiplasmodium, heme polymerase, cytotoxic, Vero cell